Energy and Acoustic Environmental Effective Approach for a Wind Farm Location - Katarzyna Wolniewicz (MDPI AG, 2021)
The justification for the construction of a wind farm depends primarily on two factors. The first one is the availability of the area with significant windiness; the second one is the environmental conditions in the selected location. The aim of this paper was to demonstrate the need for parallel noise and energy analyses during the design of a turbine location and selection of its type on the wind farm. The noise analyses were performed according to ISO 9613-2. A detailed analysis of wind conditions in a given location is a basic activity to determine the profitability of a wind power plant foundation. The main environmental impact of WF is noise emission. The examples of wind turbines’ selection optimally utilizing wind resources in two particular locations are presented. Six wind turbines were analyzed for each location. The choice of a wind turbine for the examined location was determined by the parameters of the device, the results of annual wind measurements, and acceptable noise levels in the environment. The three devices that met the acoustic criteria and the most energy efficient ones are indicated. We describe how a proper process of selecting a type of WT for a specific location should proceed.